Interpretive environmental education program in influencing secondary school students’ intention to volunteer as program organizers - Mohamed Razali, Rahmah (2017)
Many environmental education (EE) programs are still targeted at the level of raising school students’ awareness on the environment but it lack in influencing behavior. The main objective of this study is to determine the effectiveness of interpretive EE program in influencing secondary school students’ environmental volunteerism behavior, specifically involvement as an organizer of an Orangutan education program in school. The study also determines the Theory of Planned Behavior (TPB) model fitness. The study utilizes a quantitative approach by utilizing the pre-test and post-test research design. Two hundred forty-seven secondary school students from Sabah and Sarawak participated in the study. The TPB and EROT interpretive model were used to design and determined the effectiveness of an interpretive program in influencing secondary school students’ behavior Result of this study showed that the interpretive EE program is capable of influencing student’s behavioral intention towards the Orangutan and their involvement as an organizer of Orangutan education program in school. In TPB questionnaire results, significant differences were observed between pre-test and post-test for students’ behavior belief construct for both Sabah (p=0.028) and Sarawak (p=0.005). Significant difference was only observed for the behavioral intention (BI) for the Sarawak (p=0.001). In the EROT model, significant difference was observed for all construct except for students’ emotion in Sarawak while there is no significant different at all constructs in Sabah. The TPB model fitness test showed that the model fit the data and there is positive coefficient between all construct in both Sabah and Sarawak. Interpretive environmental education program is effective in influencing secondary school students to involve as an organizer of Orangutan education program in school and the model fit the data.